Alkaline Phosphatase Purification from Bacillus megaterium - Hussin, Huszalina; Hsu, W .C.; Nebenfuhr, M.; Papantoniou, C. (2012)
The aim of this study was to isolate and purify an alkaline phosphatase (ALPs) from Bacillus megaterium. The purified enzyme was established by gel filtration chromatography and high performance liquid chromatography (HPLC). Then, followed by non-denaturing gel electrophoresis to separate the ALPs from described purification technique. The purified enzyme had the following properties: ALPs concentration obtained from enzyme assay culture supernatant was 13.453ïg and selected purification techniques of gel filtration and HPLC were both 19.74ïg and 23.52ïg respectively. The enzymeâ€™s activity and specific activity from culture supernatant were both 0.493 U/ml and 36.3 U/mg respectively.